The actin regulators Enabled and Diaphanous direct distinct protrusive behaviors in different tissues during Drosophila development. - Nowotarski, S.H.; McKeon, N.; Moser, R.J.; Peifer, M. (Molecular Biology of the Cell, 2014)
Actin-based protrusions are important for signaling and migration during development and homeostasis. Defining how different tissues in vivo craft diverse protrusive behaviors using the same genomic toolkit of actin regulators is a current challenge. The actin elongation factors Diaphanous and Enabled both promote barbed-end actin polymerization and can stimulate filopodia in cultured cells. However, redundancy in mammals and Diaphanous' role in cytokinesis limited analysis of whether and how they regulate protrusions during development. We used two tissues driving Drosophila dorsal closure-migratory leading-edge (LE) and nonmigratory amnioserosal (AS) cells-as models to define how cells shape distinct protrusions during morphogenesis. We found that nonmigratory AS cells produce filopodia that are morphologically and dynamically distinct from those of LE cells. We hypothesized that differing Enabled and/or Diaphanous activity drives these differences. Combining gain- and loss-of-function with quantitative approaches revealed that Diaphanous and Enabled each regulate filopodial behavior in vivo and defined a quantitative "fingerprint"-the protrusive profile-which our data suggest is characteristic of each actin regulator. Our data suggest that LE protrusiveness is primarily Enabled driven, whereas Diaphanous plays the primary role in the AS, and reveal each has roles in dorsal closure, but its robustness ensures timely completion in their absence.